Application Of The "Crossfit" System in Sports Training of Highly Qualified Greco-Roman Style Wrestlers - Tashnazarov Jasur Yuldashevich (Zien Journals, 2022)
In order to improve the physical fitness of the Greco-Roman style wrestlers, we also used educational-training exercises in the pedagogical experiment, which varied from the developed complexes, where the educational-training work was built according to the regulated method according to the principle of circular training.
Keywords: CrossFit; physical fitness; result; efficiency